CO-RELATION OF DYSPEPSIA WITH UPPER GASTROINTESTINAL PATHOLOGY IN THE NORTHERN AREAS OF PAKISTAN - Manan, Alamzeb (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: This is a trial done over a period of two years, in which 400 patients, with persistent dyspepsia were endoscoped. The majority of the patients had gastritis. Other disorders found in order of frequency were oesophagitis duodenal ulcer and gastric ulcer. Duodenal ulcer was found to be three times more common than gastric ulcer. Carcinoma of oesophagus was found almost twice as common as carcinoma of the stomach. About one fifth of the patients has no Pathology. Compared with other studies we found that peptic ulcers, carcinoma and gastritis were more common in our study.